2021
DOI: 10.1002/alz.12308
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association between cancer and the risk of dementia: Results from the Memento cohort

Abstract: Introduction Studies on the association of cancer and risk of dementia are inconclusive due to result heterogeneity and concerns of survivor bias and unmeasured confounding. Methods This study uses data from the Memento cohort, a French multicenter cohort following persons with either mild or isolated cognitive complaints for a median of 5 years. Illness‐death models (IDMs) were used to estimate transition‐specific hazard ratios (HRs) and 95% confidence intervals (CIs) for incident cancer in relation to dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Similar to the results of Ording et al and Sun et al [ 12 , 20 ], the current study found a stronger association between cancer and the risk of ACD and VD compared to AD after further adjustment for other potentially confounding factors besides age and sex. Similar to our results, a recent prospective cohort study showed that cancer was associated with a roughly 42% reduction in risk of dementia and a 55% reduction in risk of AD [ 18 ]. In addition, a study from the Utah Population Database argued that the inverse association between cancer and AD risk arose from bias due to the competing risks of death [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to the results of Ording et al and Sun et al [ 12 , 20 ], the current study found a stronger association between cancer and the risk of ACD and VD compared to AD after further adjustment for other potentially confounding factors besides age and sex. Similar to our results, a recent prospective cohort study showed that cancer was associated with a roughly 42% reduction in risk of dementia and a 55% reduction in risk of AD [ 18 ]. In addition, a study from the Utah Population Database argued that the inverse association between cancer and AD risk arose from bias due to the competing risks of death [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Model 1 was adjusted for age and sex and model 2 was additionally adjusted for education, socioeconomic status, ApoE4 , BMI, smoking status, alcohol consumption, obesity, hypertension, diabetes, heart failure, and stroke. After adjustment for demographic characteristics (age, sex, education, socioeconomic status), BMI, smoking status, and alcohol consumption were included in model 2, taking into account the established effects on cancer-related mortality [ 18 ]. In addition, ApoE4 and some comorbidities (obesity, hypertension, diabetes, heart failure, and stroke) were also included in model 2 as risk factors for dementia [ 8 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations